2010
DOI: 10.1186/1471-2318-10-17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of valvular heart disease on activities of daily living of nonagenarians: the leiden 85-plus study a population based study

Abstract: BackgroundData on the prevalence of valvular heart disease in very old individuals are scarce and based mostly on in-hospital series. In addition, the potential detrimental effect of valvular heart disease on the activities of daily living is unknown. The present study evaluated the prevalence of significant valvular heart disease and the impact of valvular heart disease on the activities of daily living in community dwelling nonagenarians. Nested within the Leiden 85-plus study, a population based follow-up s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…For example, the Olmsted County study10 (n=298, aged 75+ years) found that 13% had an EF of 50% or less and 4% of 40% or less; the Belfrail Study20 (n=556, aged 80+ years) found 6% with an EF of 50% or less and 2% with an EF of 40% or less; the UK ECHOES study21 (n=66, aged 85+ years) found 17% with an EF of 50% or less and 3% with an EF less than 40%; and the Leiden 85-Plus Study (n=81, aged 90 years) found 9% with an EF of <50% 22. The Leiden study highlights the selection bias introduced by hospital based assessment in the very old; only 30% of those eligible were able to attend hospital for echocardiographic assessment and those who attended were significantly healthier than those who could not 22. Our findings are comparable to the recently reported Jerusalem study (n=450, aged 85 years) which reported 44% with EF less than 55% and 14% with EF less than 45% 23.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Olmsted County study10 (n=298, aged 75+ years) found that 13% had an EF of 50% or less and 4% of 40% or less; the Belfrail Study20 (n=556, aged 80+ years) found 6% with an EF of 50% or less and 2% with an EF of 40% or less; the UK ECHOES study21 (n=66, aged 85+ years) found 17% with an EF of 50% or less and 3% with an EF less than 40%; and the Leiden 85-Plus Study (n=81, aged 90 years) found 9% with an EF of <50% 22. The Leiden study highlights the selection bias introduced by hospital based assessment in the very old; only 30% of those eligible were able to attend hospital for echocardiographic assessment and those who attended were significantly healthier than those who could not 22. Our findings are comparable to the recently reported Jerusalem study (n=450, aged 85 years) which reported 44% with EF less than 55% and 14% with EF less than 45% 23.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with these results. Recently, however, Van Bemmel et al showed a high prevalence of significant VHD (70%) in a population-based sample of wellfunctioning nonagenarians [30]. Compared with the nonagenarians of the BF C80+ study (n = 51), study participants exhibited a lower prevalence of mitral stenosis (0% vs. 6%) and aortic stenosis (1% vs. 18%) and a higher prevalence of mitral regurgitation (≥moderate, 49% vs. 0%) and aortic regurgitation (≥moderate, 28% vs. 2%).…”
Section: Prevalence Of Cardiac Dysfunctionmentioning
confidence: 94%
“…These structural changes become more severe in response to chronic pressure overload from AS, and they may introduce technical complexity when deploying a transcatheter valve. Nonagenarians undergoing TAVR are also more likely to present with multi‐valve disease; with 15%‐64% exhibiting concomitant moderate or severe mitral regurgitation —a finding associated with a 2‐fold increase in mortality following TAVR . Another common yet concerning finding in nonagenarians is pulmonary hypertension; with 21%‐44% exhibiting systolic pulmonary arterial pressures >60 mmHg …”
Section: The Nonagenarian Phenotypementioning
confidence: 99%
“…The pathophysiology of calcific AS is closely connected to the aging process; with inflammaging, calcification, and repetitive mechanical stress being among the driving mechanisms . An estimated 17% of nonagenarians will develop at least mild AS over the course of their lifetime . By 2050, the number of nonagenarians is expected to quadruple to >8 million in the United States, and given that there is no proven therapy for the prevention of AS, the number of “oldest old” patients suffering from this disease is expected to mirror the demographic population trends and rise exponentially.…”
Section: Introductionmentioning
confidence: 99%